Innovative dampers as floor isolation systems for seismically-retrofit multi-storey critical facilities. (15th December 2019) - Casagrande, Lorenzo; Villa, Elena; Nespoli, Adelaide; Occhiuzzi, Antonio; Bonati, Antonio; Auricchio, Ferdinando
Highlights: Floor isolation technique is validated retrofitting critical structures. Floor isolation systems are compared with traditional base isolation systems. Sensitivity to the damper typology is explored. Locally, dampers decrease stresses in structural key members up to 38%. Globally, floor isolation attenuates top displacements up to 41%. Abstract: Code provisions are intended to guide engineers to design new buildings adequately protected against structural failures; however, in critical facilities (such as power plants, military headquarters, hospitals, etc.) the post-emergency operability is maintained not only preserving structural integrity but also safeguarding the content functionality. As a result, the present work aims to investigate the use/effectiveness of a method to retrofit existing strategical buildings: in detail, the suggested procedure consists in installing cutting-edge dampers to isolate selected floor systems on a set of multi-storey frames, decoupling fragile nonstructural contents from the seismic source. Initially, taking advantage of peculiar properties of innovative shape-memory alloy materials, we design dampers capable to remain elastic for low-intensity dynamic events, combining 3D finite element numerical simulations to experimental tests performed at the Italian National Research Council (CNR). Subsequently, visco-elastomeric dampers are proposed in order to achieve comparable dissipative performances. Finally, we calibrate equivalent monodimensional FE link-like elements to study building global response and to reproduce the dynamics of floor isolation systems (FISs). Results provide evidence on the local and global seismic response attenuation due to FISs, in terms of stress and deformation reduction. Floor isolation effectiveness is highlighted, comparing visco-elastomeric with SMA dampers, both in a deterministic and in a statistic perspective.